Pengaruh Employee Well-being dan Job Satisfaction terhadap Employee Performance - Ariesto Patria Sabil (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2021)
In this globalization era, every corporation works hard to increase and develop to boost their employee performance. There are lot of factors corporation has to take care to increase their employee performance. This research probes employee well-being and job satisfaction as independent variables to employee performance as dependent variables. The selection method of the sample is using purposive sampling and obtained 95 samples from the population of the whole employee of the corporation using a questionnaire to collect the samples.SPSS 26 from IBM is being used for the multiple linear regression analysis techniques. A significant and positive effect is discovered from job satisfaction to employee performance, while employee well-being has a non-significant effect. The company should consider their employee job satisfaction in order to increase company's performance.